Triggering of Transmural Infarctions, but Not Nontransmural Infarctions, by Ambient Fine Particles - Rich, David Q.; Kipen, Howard M.; Zhang, Junfeng; Kamat, Leena; Wilson, Alan C.; Kostis, John B. (Environmental health perspectives, 2010)
Background: Previous studies have reported increased risk of myocardial infarction (MI) after increases in ambient particulate matter (PM) air pollution concentrations in the hours and days before MI onset. Objectives: We hypothesized that acute increases in fine PM with aerodynamic diameter ≤ 2.5 μm (PM2.5) may be associated with increased risk of MI and that chronic obstructive pulmonary disease (COPD) and diabetes may increase susceptibility to PM2.5. We also explored whether both transmural and nontransmural infarctions were acutely associated with ambient PM2.5 concentrations. Methods: We studied all hospital admissions from 2004 through 2006 for first acute MI of adult residents of New Jersey who lived within 10 km of a PM2.5 monitoring site (n = 5,864), as well as ambient measurements of PM2.5, nitrogen dioxide, sulfur dioxide, carbon monoxide, and ozone. Results: Using a time-stratified case-crossover design and conditional logistic regression showed that each interquartile-range increase in PM2.5 concentration (10.8 μg/m³) in the 24 hr before arriving at the emergency department for MI was not associated with MI overall but was associated with an increased relative risk of a transmural infarction. We found no association between the same increase in PM2.5 and nontransmural infarction. Further, subjects with COPD appeared to be particularly susceptible, but those with diabetes were not. Conclusions: This PM—transmural infarction association is consistent with earlier studies of PM and MI. The lack of association with nontransmural infarction suggests that future studies that investigate the triggering of MI by ambient PM2.5 concentrations should be stratified by infarction type.